Outsourcing transformation: the social justice impact of diversity interventions in privileged South African schools - Willand, Julia (My University, 2022)
The apartheid-legislated racial inequality enforced through the Bantu education system lives on today with privileged schools still being untransformed, inadequately geared towards the needs of Black learners and representing sites of daily violence against them. Inspired by the student protests which started in 2015, schools have increasingly been called out for their lack of transformation, and a number of them have started engaging diversity consultants. By examining participants’ perceptions and applying critical race and critical diversity theoretical lenses, this qualitative study explores the schools’ rationale and expectations of diversity consultants, the risks and possibilities that diversity interventions hold for transformational social justice at these schools, and the ways in which hegemonic power structures are disrupted or kept in place. The findings expose how interventions allow schools to merely perform transformation and exacerbate certain harm, but also illuminate how interventions can help untangle (albeit at a glacial pace) the thick webs of violent White ignorance and strategies of resistance. The #FeesMustFall and #BlackLivesMatter protests and related social media storms both conscientized learners and placed pressure on the schools. In combination with facilitated interventions this allowed for more critical and racially literate language across stakeholders, enabling a more robust and effective engagement with questions of race, power and transformational social justice. Through this, learners and alumni are found to have achieved a partial reversal of the privatization of diversity, turning the discourse around race back towards a more civil rights-based one in the “public sphere” and enabling transparent societal debate. The study further finds that the pressure of protests and the power of social media have allowed (and required) Black learners/alumni to step into the role of educators, bringing about what might be the start of an incremental counter-hegemonic power shift along the lines of race, intra-system position and seniority, in which the terms of who does transformation, and how, are no longer solely determined by White people in authority.
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Arts in Critical Diversity Studies to the Faculty of Humanities, School of Social Science, University of Witwatersrand, Johannesburg, 2022